Detecting NiTi two-way shape memory effect based on microstructural and macromechanical parameters. Issue 3 (11th February 2019) - Urbina, C.; Gispert, F.; Ferrando, F.; De la Flor, S.
ABSTRACT: The two-way shape memory effect in NiTi shape memory alloys is identified according to the evolution of the apparent modulus of the martensite during mechanical cycling. The microstrain and texture index of the NiTi samples are evaluated with synchrotron data to relate the evolution to the changes in the NiTi microstructure caused by mechanical cycling. The results show that a progressive decrease in the apparent modulus of the martensite during load, together with an increase in the apparent modulus of the reoriented martensite, are a sign that the NiTi sample is developing the two-way memory effect by mechanical cycling. When the two moduli show the same value, the two-way shape memory effect is fully developed in the NiTi alloy. This paper is part of a thematic issue on Titanium.